2015
DOI: 10.1080/10509674.2015.1025177
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family Service Involvement on Treatment Completion and General Recidivism Among Male Youthful Sexual Offenders

Abstract: Few studies have systematically evaluated outcomes of services for youth with sexually problematic behaviors. Evaluations are particularly sparse for youth receiving family-oriented treatment despite an increased emphasis on family in healing and rehabilitation contexts. There are common approaches to family inclusion that have been argued by field professionals as "best practice," and this study quantitatively investigates the usefulness of such approaches. With support from the state Sex Offender Management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…A latent barrier to family treatment is the finding that youth who commit sexual crimes tend to have low levels of family involvement (Efta-Breitbach & Freeman, 2004). Still, family involvement in treatment for sexually offending youth has been found to be an inherent protective factor against recidivism, and family participation yields higher rates of successful treatment completion by youth (Yoder et al, 2015). Family treatment may strengthen protective properties in the parent-child relationship and home environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A latent barrier to family treatment is the finding that youth who commit sexual crimes tend to have low levels of family involvement (Efta-Breitbach & Freeman, 2004). Still, family involvement in treatment for sexually offending youth has been found to be an inherent protective factor against recidivism, and family participation yields higher rates of successful treatment completion by youth (Yoder et al, 2015). Family treatment may strengthen protective properties in the parent-child relationship and home environment.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed on family-oriented approaches to prevention and treatment programs. While programs like Multisystemic Therapy have been tested and proven effective (Letourneau et al, 2013), and other family-oriented community-based treatments have shown promise (Yoder et al, 2015), there are variations of family service delivery that can be tested, and certainly more research can be done on how to successfully engage and maintain involvement in treatment (Yoder, 2014). Furthermore, the field surrounding youth who commit sexual crimes has yet to fully test the impact of poly-victimization on youth sexual offending.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many have contextualized sexual offending behaviors through a family-oriented lens (Burton, Smith-Darden, & Frankel, 2006;Friedrich, 2007;Schladale, 2006;Thomas, 2004Thomas, , 2010. Researchers have also documented the critical influence family can play in shaping treatment outcomes for youth sexual offenders (Yoder, Hansen, Lobanov-Rostovsky, & Ruch, 2015). So, understanding the family, particularly parent-child relationships, can be essential to broader conceptualizations of the problem of youth sexual offending.…”
Section: Discussionmentioning
confidence: 99%
“…As these findings are replicated, treatment agencies can begin to target family-level attachment characteristics through multi-modal intervention approaches (Fortune, Ward, & Print, 2014). As research has begun to show the positive impact of family-based models for youth sexual offenders (Letourneau et al, 2013; Yoder et al, 2015), it becomes increasingly important to amalgamate families into the treatment context to advance best practices in the field (Longo & Prescott, 2006). Furthermore, it may be necessary to deeply dissect family attachments within treatment to enhance communication skills with parents and reduce feelings of anger and alienation (Yoder & Ruch, 2016).…”
Section: Discussionmentioning
confidence: 99%